THE RELATIONSHIP BETWEEN ELEMENTARY SCHOOL CHILDREN’S VISUAL ACUITY AND ONLINE SCHOOL ACTIVITIES OVER 2 YEARS - nur fadilah fikriyyah Shandy; Miftahul Akhyar Latief (RS Mata Makassar, 2024)
Background : Based on WHO data (2020), it is estimated that almost 18.9 million children under the age of 15 years experience impaired visual acuity. In general, the main cause of visual impairment is refractive errors that cannot be corrected (myopia, hyperopia and astigmatism), while cataracts are the main cause of blindness. Objective : To determine the relationship between elementary school children’s visual acuity and online school activities for 2 years. Methods : A Descriptive Retrospective study aims to determine the characteristics of glaucoma sufferers at Makassar Eye Hospital in 2019-2021 using a purposive sampling method. Results : The results of this research are that there is a significant relationship between elementary school children’s visual acuity and online school activities of 0.010 (< 0.05). These results mean that there is rejection of H0, or there is a relationship between the two variables. Conclusion : Based on the results of the research that has been obtained along with the discussion that has been made, it can be concluded that there is a significant relationship between elementary school children’s visual acuity and online school activities in elementary school students in grades 5 and 6.